PEMUTUSAN HUBUNGAN KERJA OLEH PERUSAHAAN TERHADAP PERSELISIHAN HUBUNGAN INDUSTRIAL DI INDONESIA - Yusmedi Yusuf; Muhammad Rizqi Fadhlillah; Rommy Pratama (SUPREMASI HUKUM, 2022)
Termination of employment by companies is a dynamic of industrial relations for actors in the process of producing goods and services between workers, employers, and the government. The company has a socio economic nature in carrying out industrial relations, dealing with the juridical aspects that apply in Indonesia. The company terminates the employment relationship unilaterally, causing suffering to the workers because they lose their livelihood for their lives and their families. Labor laws and regulations in Indonesia have not been effective and have caused many problems in implementing harmonious industrial relations. Government interference as a power organization can provide protection for workers affected by termination of employment by the company. Keywords: Termination of Employment, Industrial Relations Disputes